Case report: Unilateral paralysis of the hypoglossal nerve as the only clinical sign of clivus meningioma - a case report and literature review - Stamenović, Jelena; Živadinović, Biljana; Đurić, Vanja (Frontiers in Oncology, 2024)
Introduction Clivus meningiomas are benign tumors that occur at the skull base in the posterior cranial fossa. Symptoms usually progress several months or years before diagnosis and may include: headache, vertigo, hearing impairment, ataxia with gait disturbances, sensory problems. In the neurological findings, paralysis of the lower cranial nerves is most often seen, which in the later course can be accompanied by cerebellar and pyramidal signs until the development of a consciousness impairment. Case presentation We presented the case of a patient who at the time of diagnosis had only unilateral hypoglossal nerve paralysis with dysarthria and mild dysphagia. After the neurosurgical procedure, pathohistological analysis confirmed meningothelial meningioma. Conclusion Early recognition of clivus tumors, which include meningiomas, is necessary in order to implement an adequate therapeutic procedure and prevent further deterioration of the patient’s condition.